Long-term results of complex treatment of children with postoperative intra-abdominal infiltrates - Melnychenko, M.; Antonyuk, V.; Eliy, L. (Journal of Education, Health and Sport, 2017)
Introduction. Based on the results of our own clinical studies, we have developed a program for comprehensive diagnosis and treatment of postoperative intra-abdominal infiltration in children with appendicular peritonitis by using a diagnostic algorithm and complex saving measures in a hospital setting and at the stage of ambulatory-polyclinic treatment. Aim: To study the remote results of children's treatment with postoperative intra-abdominal infiltrates. Material and methods. With the help of quasi-monitoring, we have received information about the state of 109 children one year after inpatient treatment. Complex treatment of children was carried out according to the program we have developed. Results. Combined use of therapeutic and physical factors in the complex treatment of children with PII, using the developed program in conditions of inpatient and outpatient treatment favorably affected the restoration of impaired functions of the child's body in general and specifically of the abdominal organs, providing a higher effect compared to patients receiving limited complex treatment Conclusions. Disappearance of palpated "tumor", ultrasound signs of intra-abdominal infiltration and the occurrence of adhesive intestinal obstruction can be considered as the main clinical response throughout the treatment process. Final analysis of the late period results of integrated treatment indicated a probable increase in the number of MG patients with an overall assessment of the outcome of the treatment as "good" (95.1% of children versus 72.1% in the CG) and a decrease in the "unsatisfactory" outcome of treatment in 2 times among children of MG (2.4%) against children of the CG (4.4%). Primary laparoscopic intervention in children (CS 2, MS 2) contributed to the favorable course of the disease, and after ambulatory-polyclinic treatment resulted in the absence of "unsatisfactory" results.